The frequency of vitamin B12 derangements in females presenting for workup of iron deficiency anemia - Atzaz, Noreen; Khattak, Mehnaz; Zuhra, Fatimah Tuz; Afzal, Javeria; Khaliq, Sehar; Saeed, Sami (Journal of Rawalpindi Medical College, 2023)
Objective: Iron deficiency anemia (IDA) is the most prevalent hematological disorder in women of child-bearing age. IDA poses a threat to feto-maternal wellbeing. It is the leading cause of morbidity and mortality in pregnancy. IDA in young females can coexist with other nutritional deficiencies such as vitamin B12 (Vit B12). An undetected Vit B12 deficiency carries a greater likelihood of development of maternal neuropsychiatric disorders and neural tube defects in the fetus. Materials and methods: Venous blood samples of non-pregnant female population (N=133) from Fauji Foundation Hospital, Rawalpindi were collected and analyzed for complete blood count (CBC), Vit B12 and serum Ferritin. Population was further subdivided into two groups. Group A, included females with low serum Ferritin and low MCV, group B restricted to normal serum Ferritin and low MCV, whereas control group had females with normal serum Ferritin and MCV levels. Results: Demographic data suggested that only height was slightly lower in IDA patients other than reduced serum Ferritin levels. Group A also showed reduced levels of Vit B12 as compared to group B and control group. CBC analysis indicated marked reduction in all hematological parameters except platelet count in group A. Conclusion: Our findings suggest that IDA and Vit B12 deficiency may coexist in young females. Monitoring Vit B12 along with iron deficiency parameters is essential to treat anemia and prevent gynecological complications. Paucity of information on their coexistence in females of childbearing age require further investigation. Keywords: Vitamin B12, Iron deficiency anemia, Microcytosis, Serum Ferritin.